Pengaruh Ketergantungan Nikotin Terhadap Kadar Trigliserida Pada Perokok yang Terdiagnosis Hipertensi - Sudarsono, Erica Kusuma Rahayu; Patramurti, Christine (Jurnal Farmasi Udayana; Vol. 12, No. 2, tahun 2023DO - 10.24843/JFU.2023.v12.i02.p06, 2024)
Cardiovascular disease was one of the leading causes of world death. Cardiovascular disease accounts for 35% of total deaths in Indonesia. People who smoke have a greater risk of developing cardiovascular disease because smoking lead to an increase of lipolysis and triglyceride levels. The triglycerides levels are an early marker of increasing remnant cholesterol that caused cardiovascular disease. This research is an analytic observational study with a cross-sectional approach which was conducted on 31 hypertensive male smokers. The purpose of this study was to determine the effect of nicotine dependence on triglyceride levels as an early marker of increased cardiovascular risk. Nicotine dependency was analyzed using Fagerstorm Test for Nicotine Dependence (FTND). The effect of the nicotine dependence on triglyceride levels was analyzed using Fisher's test so that the odds ratio and p-value were obtained. The results showed that respondents with high nicotine dependence seems to had a higher risk of increasing triglyceride levels above the normal limit 0,333 times (OR 0,333; 95% CI 0,051-2,177) greater than low nicotine dependence although not statistically significant (p-value 0,370).